Social isolation, loneliness, and their correlates in older Japanese adults. Issue 3 (26th March 2023) - Kino, Shiho; Stickley, Andrew; Arakawa, Yuki; Saito, Masashige; Saito, Tami; Kondo, Naoki
Abstract : Background: Loneliness and social isolation are elevated in older adults and associated with a range of detrimental outcomes. Despite this, there has been little research on these phenomena or on similarities and differences in their occurrence or combination in older Japanese adults. The current study aims to (i) determine what factors are associated with social isolation and loneliness among older adults in Japan; and (ii) describe the characteristics of individuals who are socially isolated but not lonely, as well as those who feel lonely but are not socially isolated. Methods: Data were analysed from 13 766 adults aged ≥65 years who participated in the 2019 wave of the Japan Gerontological Evaluation Study. Poisson regression analysis was used to examine associations. Results: Among older Japanese adults, the attributes of higher age, male gender, lower socioeconomic status, being a welfare recipient, and having depressive symptoms were associated with social isolation, while lower socioeconomic status, unemployment, welfare receipt, and poor physical and mental health were associated with loneliness. In addition, better educated, and mentally and physically healthy people were less likely to feel lonely even when socially isolated, while people who were not working and who had mental or physical health problems were more likely to feel lonely even if they were not socially isolated. Discussion: Our results indicate that in order to reduce unwanted social isolation and loneliness among older Japanese adults, in the first instance the focus should be on those individuals who are socioeconomically disadvantaged and unhealthy.